Digital Collections and Digital Collecting Practices - Watkins, Rebecca D.; Sellen, Abigail; Lindley, Siân (33rd Annual ACM Conference on Human Factors in Computing Systems, 2015)
Reference is increasingly made to ‘digital collections’, yet this term encompasses accumulated digital objects of varying form, purpose and value. We review social science literature on material collections and draw from in-depth interviews with 20 people in the UK in order to offer a clearer understanding of what constitutes a digital collection and what does not. We develop a taxonomy that presents three distinct types of digital collection and demonstrate ways in which the affordances of digital environments may facilitate or impede meaningful practices of acquisition, curation and exhibition in each case. Through doing so, we present a framework for design in support of collecting practices and the development of more meaningful and valued digital collections.